Faking it with the firefighter - Dove, Rachel (Harlequin medical romance, 2025)
Following a dramatic breakup, Lexi Olsen thinks that becoming lead paramedic at New York's Firehouse 17 is the ideal fresh start. The flirtatious friendship that develops with her handsome colleague Alex Morrison is a bonus-even though Lexie has vowed to never have a relationship again. Firefighter Alex, still grieving his ex-wife, is also too broken for romance, but when Lexie's cheating ex joins the team demanding another chance, agreeing to pretend date Lexi is the only way to shut her ex down! With their red-hot and off-limits attraction becoming more undeniable, could they be playing with fire?